PENGARUH INTENSITAS KONSUMSI INFORMASI E-WOM E-WALLET, INTENSITAS KOMUNIKASI E-WOM E-WALLET, PERSEPSI MANFAAT DAN PERSEPSI KEMUDAHAN PENGGUNAAN TERHADAP MINAT MENGGUNAKAN APLIKASI E-WALLET - Dhea Ayu Fairuzha; Lintang Ratri Rahmiaji; S. Rouli Manalu (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2023)
Technological developments encourage changes in the behavior of people's transactions in Indonesia. Currently, people are starting to switch to non-cash transactions. The use of e-wallets has now become a new phenomenon in the world of finance and technology. The emergence of the phenomenon of using e-wallets has encouraged various digital wallet companies in Indonesia. As a result of this competition, each e-wallet company has improved the performance of its features and services as well as increased the dissemination of information in various mass media such as television, radio, online news and Instagram social media. Even so, not all people use e-wallets to make payment transactions. The study aims to determine the effect of the intensity of e-wallet information consumption, the intensity of e-wom e-wallet communication, perceived usefulness and perceived ease of use on interest in using e-wallet applications. This study uses the Technology Acceptance Model (TAM) and simple linear regression statistical tests. The sample in the study was 100 respondents aged 20-60 years who are residents of the city of Semarang. The results of the study prove that in H1 there is an influence between the intensity of consumption of e-wallet information on perceived usefulness. Then, in H2 there is an influence between the intensity of e-wom e-wallet communication on perceived usefulness. In H4 there is an influence between the intensity of e-wom e-wallet communication on perceived ease of use. Then, in H5 there is an influence between perceived usefulness on interest in using e-wallet applications, and in H6 there is an influence between perceived ease of use and interest in using e-wallet applications. Meanwhile, in H3 it shows that there is no influence between the intensity of consumption of e-wallet information on perceived ease of use, which means that the perceived ease of use of individuals does not grow from the intensity of consumption of e-wallet information, instead the intensity of e-wom e-wallet communication contributes to the growth perceived ease of use.